1991
DOI: 10.1093/ndt/6.1.5
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Vascular Access for Haemodialysis in The Netherlands

Abstract: After nearly 30 years of access surgery for haemodialysis, a survey of vascular access in a large population seemed relevant in order to analyse the state of the art. On 1 January 1988, 2195 patients in 52 centres in The Netherlands (population 14,714,900) were on long-term haemodialysis and 588 on continuous ambulant peritoneal dialysis (CAPD) for renal insufficiency. A questionnaire was mailed out, to which there was 100% response. Of all the patients on long-term haemodialysis, 70% had a Cimino fistula, 22%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(13 citation statements)
references
References 0 publications
1
11
0
1
Order By: Relevance
“…In the present material, in 86.8 % patients the lesions developed in the presence of the above underlying diseases and only in less than 5 % (4.1 %), diabetic nephropathy was responsible for renal failure. The above data approximate findings from the literature; where at present, diabetic nephropathy accounts for a low percentage of causes of CRF; what is an evidence of progress having occurred over the years in proper management of diabetic patients [1113, 20, 21]. …”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the present material, in 86.8 % patients the lesions developed in the presence of the above underlying diseases and only in less than 5 % (4.1 %), diabetic nephropathy was responsible for renal failure. The above data approximate findings from the literature; where at present, diabetic nephropathy accounts for a low percentage of causes of CRF; what is an evidence of progress having occurred over the years in proper management of diabetic patients [1113, 20, 21]. …”
Section: Discussionsupporting
confidence: 85%
“…Such a situation may pose an additional threat to the cardiac muscle and the entire circulatory system [610]. According to the data from the literature on the subject, between 15 % and approximately 40 % of patients require dialysis therapy and its duration is often positively correlated with the insensitive to conservative therapy nodular (monoclonal) type of parathyroid proliferation [1113]. In such cases, a factor that plays a decisive role in the therapeutic success is a properly planned and executed surgical procedure, which—through interrupting autonomous PTH release allows for a possibility of regulating the level of phosphates and calcium as well as provides creates favorable conditions for a kidney transplant [14].…”
Section: Introductionmentioning
confidence: 99%
“…This goal has been surpassed in almost all European countries. In a survey performed in The Netherlands [2], among 52 centers, 76% of the patients on long-term hemodialysis had autologous AV fistulae. The Catalan Renal Registry [3] also revealed that in 85% of 3,073 hemodialyzed patients an AV fistula was used.…”
Section: Discussionmentioning
confidence: 99%
“…Since the late 1980s AVFs have been used by 60-65% of the haemodialysis patients in the Netherlands [7,8]. Moreover, a national survey we held in 2002-03 displayed not only an unchanged percentage of AVF use (59%), but also a great range in both type of vascular access use (AVFs: 31-91% and grafts: 3-57%) and anatomical location.…”
Section: Introductionmentioning
confidence: 98%